(3GdTaG aj HOjY GdGcJaGs - (3eMeO Hf MSf Hf Ydj Hf YKeGf GdfhGLj GdTGaYj , TeS GdOjf,J (B859 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdPi eG NGH ef EcJai Hg agPg fHPg ef GdEcJaGA YRjRI GdebGd cGfJ CRGgQ ai QjkG ef GdCOH efKhQI aLeYJgG s
(3BNQgG (B:s
(3CHUQJ djdkG hfgGQkG eYkG jG bhe eG CMSf gPG GdbQG Je cJGH GdTaG s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3eUOQ GbJfGA GdCUd (B:s
(3eOQjO (B(433) s
Keywords: (3GdHdGZIs